PENYUSUNAN FORMULIR NASABAH, SLIP SETORAN TABUNGAN, DAN BUKU TABUNGAN (BUMDes) (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
The program for preparing customer registration forms, deposit slips, and passbooks at BUMDes is needed to add programs available on BUMDes for the progress of the BUMDes themselves. The purpose of the customer registration form itself is clear, namely for recording the identity of prospective customers in a file tailored to the identity given by the customer to the BUMDes management.The purpose of the Passbook is a note or record of incoming and outgoing funds, along with interest in each transaction in writing and witnessed by customers and management of BUMDes. The deposit slip as a note in the form of two copies, the purpose of this two-fold note is also proof that the customer has deposited the funds to the BUMDes management, so the first slip is given to the customer and the other is given to the BUMDes management as an archive.This program hopes to be able to help the community in depositing funds, which is more precisely the program.